Investigating the Mutagenic Effects of Three Commonly Used Pulpotomy Agents Using the Ames Test - Mohammad Samiei; Saeed Asgary; Malak Farajzadeh; Nasrin Bargahi; Majid Abdolrahimi; Usef Kananizadeh; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2015)
Purpose: The mutagenic potency of materials used in dentistry is of great concern. The Ames test is a bacterial reverse mutation assay, which is used to determine the mutagenicity potential of chemicals. In this study, the Ames test was used to compare mutagenic effects of three pulpotomy agents, namely, CEM cement, formocresol and ferric sulfate. Methods: TA100 strain of Salmonella typhimurium was used to evaluate mutagenicity of different concentrations of pulpotomy materials in the presence and absence of enzymatic system found in rat liver S9 fraction. Negative controls were 1% dimethyl sulfoxide and water. The positive controls were sodium azide and 2-aminoanthracene. The number of colonies per plate was counted. The material was regarded mutagenic if the number of histidine revertant colonies was twice or more than the spontaneous revertant colonies (Ames mutagenicity ratio). Results: Ferric sulfate was found mutagenic in the concentrations prepared by addition of 50 μL of its 1 in 100 and 1 in 1000 times diluted solutions to the culture medium in the absence of S9 fraction (Ames test ratios of 2.8 and 2.2, respectively). Formocresol showed strong toxicity toward TA100 strain of S. typhimurium up to the concentration as low achieved using 1000 times diluted solution of the original preparation, particularly in the presence of S9 fraction. Ames assay failed to detect significant reverse mutations in all the concentrations of CEM cement. Conclusion: In contrast to formocresol and ferric sulfate, CEM cement is a less toxic and non-mutagenic agent.